Does Loneliness Necessarily Lead to a Decrease in Prosocial Behavior? The Roles of Gender and Situation - Huang, Heqing; Liu, Yanchun; Liu, Xiaocen (Frontiers in Psychology, 2016)
Although previous studies show overwhelming evidence that loneliness is negatively correlated with prosocial behavior, some theories and research have implied that under certain situations, loneliness plays a positive role in an individual’s social functioning. The two studies reported in this article examined loneliness and its associations with prosocial behavior in Chinese adults using subjective reporting and experimental design. Study 1 examined 305 Chinese adults (175 males) using the Social and Emotional Loneliness Scale for Adults and the Prosocial Tendencies Measure to evaluate their loneliness and prosocial tendencies. The results showed that loneliness was negatively associated with all prosocial tendencies except the public prosocial tendency. Study 2 examined 177 Chinese adults (61 males) using an experimental design and found that only lonely women in public situations expressed a greater willingness to help. The results also suggest that loneliness may play a positive role in the social functioning of individuals under certain conditions. The function of loneliness and the implications of the association between loneliness and prosocial behavior are discussed.